A Classroom Experience That Builds the Top Skills Employers Want. (June 2016) - Smith, Kirk
National surveys routinely list the skills employers look for in new college graduates. This article describes a classroom activity that helps build those skills in your students but does not require dedicating your whole course to the effort. Guests from the business world visit class for only 1 hour and bring real problems for the students to work on while the client visits. Students must quickly analyze the client's situation, develop possible solutions in a team and time-pressured environment, and then present their ideas to the guest within that hour. Nine iterations during the semester seems to be enough.